2015
DOI: 10.2147/sccaa.s80157
|View full text |Cite
|
Sign up to set email alerts
|

Regulators of pluripotency and their implications in regenerative medicine

Abstract: The ultimate goal of regenerative medicine is to replace damaged tissues with new functioning ones. This can potentially be accomplished by stem cell transplantation. While stem cell transplantation for blood diseases has been increasingly successful, widespread application of stem cell therapy in the clinic has shown limited results. Despite successful efforts to refine existing methodologies and to develop better ones for reprogramming, clinical application of stem cell therapy suffers from issues related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 128 publications
(153 reference statements)
1
10
0
Order By: Relevance
“…Stem cell therapy represents a highly promising new modality of treatment for advanced diabetes. However, many concerns about the type of stem cells, the transplantation procedure, and long-term recovery remain to be addressed [ 6 ]. Numerous in vivo animal studies demonstrated the potential advantages of using stem cells to treat DM.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cell therapy represents a highly promising new modality of treatment for advanced diabetes. However, many concerns about the type of stem cells, the transplantation procedure, and long-term recovery remain to be addressed [ 6 ]. Numerous in vivo animal studies demonstrated the potential advantages of using stem cells to treat DM.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer progression seems to be mediated by a subgroup of these cells, mesenchymal stem cells (MSCs). MSCs are multipotent cells capable of differentiating into numerous cell types, including adipocytes, osteoblasts, chondrocytes, fibroblasts, and perivascular and vascular structures [ 2 ]. In addition to their high regenerative capacities [ 3 , 4 ], MSCs have also been reported to be among the cells recruited in large numbers to the stroma of developing tumors [ 5 8 ] and subsequently have important microenvironmental roles in modulating tumor progression and drug sensitivity [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Telomerase and its core component hTERT are critical for stem cell compartment integrity ( El-Badawy and El-Badri, 2015 ). Normal adult stem cells are known to have the longest telomeres in a given tissue, which is mediated by the upregulation of hTERT ( Flores et al, 2006 ; Hiyama and Hiyama, 2007 ).…”
Section: Discussionmentioning
confidence: 99%